Endocrine systems of the skin - Leis, Kamil; Mazur, Ewelina; Jabłońska, Magdalena; Kolan, Michalina; Gałązka, Przemysław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
Apart from its protective function, the skin is also both hormonally and metabolically active. Many hormones are produced in the skin and the regulation of these changes is controlled, as are other organs, by the pituitary gland and hypothalamus. Under the influence of stress factors such as ultraviolet radiation, many reactions are stimulated. After exposure to light in keratinocytes apart from eumelanin, also proopiomelanocortin, dopamine, and opioid substances – β-endorphins are produced. The skin also has a hypothalamic-pituitary-adrenal axis homolog. A corticotropin-releasing hormone is produced and reacts with its skin receptors that lead to, among others, increasing vascular permeability or induce keratinocytes differentiation. A similar homologous system found in skin structures is the hypothalamic-pituitary-thyroid axis, which is expressed by the presence of e.g. thyroid-stimulating hormone (TSH) receptors or thyroglobulin genes. Our review presents selected hormonal skin systems, reactions within them and their products.